NET Release of Long-Term Surviving Neutrophils - Kolman, Jan Philipp; Pagerols Raluy, Laia; Müller, Ingo; Nikolaev, Viacheslav O.; Trochimiuk, Magdalena; Appl, Birgit; Wadehn, Hannah; Dücker, Charlotte Maria; Stoll, Fabian David; Boettcher, Michael; Reinshagen, Konrad; Trah, Julian (Frontiers in Immunology, 2022)
Background: Neutrophil extracellular traps (NETs)—as double-edged swords of innate immunity—are involved in numerous processes such as infection, inflammation and tissue repair. Research on neutrophil granulocytes is limited because of their short lifetime of only a few hours. Several attempts have been made to prolong the half-life of neutrophils using cytokines and bacterial products and have shown promising results. These long-term surviving neutrophils are reported to maintain phagocytic activity and cytokine release; however, little is known regarding their capability to release NETs. Methods: We analysed the prolongation of neutrophil survival in vitro under various culture conditions using granulocyte colony-stimulating factor (G-CSF), lipopolysaccharide (LPS) or tumour necrosis factor alpha (TNF-α) by flow cytometry and a viability assay. Additionally, we assessed NET formation following stimulation with phorbol 12-myristate 13-acetate (PMA) by immunofluorescence staining, myeloperoxidase (MPO)-DNA sandwich-ELISA and fluorometric assays for cell-free DNA (cfDNA), neutrophil elastase (NE) and myeloperoxidase (MPO). Results: Untreated neutrophils could form NETs after stimulation with PMA for up to 24 h. Incubation with LPS extended their ability to form NETs for up to 48 h. At 48 h, NET release of neutrophils cultured with LPS was significantly higher compared to that of untreated cells; however, no significantly different enzymatic activity of NE and MPO was observed. Similarly, incubation with G-CSF resulted in significantly higher NET release at 48 h compared to untreated cells. Furthermore, cells showed significantly higher enzymatic activity of NE and MPO after incubation with G-CSF. Lastly, incubation with TNF-α had no influence on NET release compared to untreated cells although survival counts were altered by TNF-α. Conclusions: G-CSF, LPS, or TNF-α each at low concentrations lead to prolonged survival of cultured neutrophils, resulting in considerable differences in NET formation and composition. These results provide new information for the use of neutrophils in long-term experiments for NET formation and provide novel insights for neutrophil behaviour under inflammatory conditions.